2012
DOI: 10.1016/j.jcrs.2011.09.046
|View full text |Cite
|
Sign up to set email alerts
|

Graft profile and thickness as a function of cut transition speed in Descemet-stripping automated endothelial keratoplasty

Abstract: Reducing the transition speed in microkeratome dissection produced thinner donor lenticules. Thickness asymmetry is an inherent flaw with current microkeratome dissection that cannot be easily corrected by altering preparation technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…Our technique of using a 400 μm microkeratome head does not have a learning curve for surgeons who are already using an artificial AC for preparation of a DSAEK donor lenticule. It has been shown previously that a slow microkeratome pass speed produced significantly thinner donor lenticules than the standard pass speed . Furthermore, our technique is more economical as compared with the double pass technique and bereft of the possible complications associated with the double pass technique.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Our technique of using a 400 μm microkeratome head does not have a learning curve for surgeons who are already using an artificial AC for preparation of a DSAEK donor lenticule. It has been shown previously that a slow microkeratome pass speed produced significantly thinner donor lenticules than the standard pass speed . Furthermore, our technique is more economical as compared with the double pass technique and bereft of the possible complications associated with the double pass technique.…”
Section: Discussionmentioning
confidence: 72%
“…It has been shown previously that a slow microkeratome pass speed produced significantly thinner donor lenticules than the standard pass speed. 12 Furthermore, our technique is more economical as compared with the double pass technique and bereft of the possible complications associated with the double pass technique.…”
Section: Discussionmentioning
confidence: 94%
“…Control of the IP in microkeratome cutting has not been standardized, and various methods have been used including adjusting hydrostatic pressure by elevating a balanced salt solution bottle, 10 , 11 , 19 inflating with air from a syringe, 2 , 3 , 7 , 8 , 19 and ocular tonometry measuring a tonometer. 13 , 20 , 21 We found that IP control using the conventional method produced high variation in IP level during cutting, and the peak IP levels varied among cuts ( Figs. 1A and 1C ).…”
Section: Discussionmentioning
confidence: 87%
“…23 A recent report shows that alteration in the posterior astigmatism at least in part may be intrinsic to microkeratome donor preparation. 24 …”
Section: Discussionmentioning
confidence: 99%